Tajemnicze bóle kręgosłupa odcinka lędźwiowo-krzyżowego - Marcinkowski, Jerzy Tadeusz (1948- ) - red.; Konopielko, Zofia - red.; Rosińska, Paulina; Klimberg, Aneta; Konopielko, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The monograph discusses: the epidemiology of low back pain (LBP), types of pain, risk, diagnosis, disability, osteoporosis in children, problems of the elderly, new research on intervertebral disc degeneration, psychosocial determinants, pain memory, emotional well-being, prevention and treatment.
Keywords: LBP; ból dolnego odcinka kręgosłupa; ryzyko; diagnostyka; osteoporoza dzieci; dobrostan; pain; risk; diagnosis; osteoporosis in children; well-being